Tongue function and its influence on masticatory performance in patients treated for oral cancer: a five-year prospective study. - de Groot, Reilly J.; Merkx, Matthias A.W.; Hamann, Merel N.S.; Brand, Henk S.; de Haan, Anton F.J.; Rosenberg, Antoine J.W.P.; Speksnijder, Caroline M. (Supportive Care in Cancer, 2020)
Purpose: The purpose of this study was to observe the impact of oral oncological treatment, including the recovery of several tongue functions (force, mobility, and sensory functions), and to determine the influence of these functions on masticatory performance.Materials and Methods: Masticatory performance and tongue force, mobility, and sensory functions were determined in 123 patients with oral cavity cancer. The assessments were performed 4 weeks before treatment and 4 to 6 weeks, 6 months, 1 year, and 5 years after treatment. Generalized estimation equations and mixed model analyses were performed, correcting for previously identified factors in the same population.Results: A significant deterioration in tongue mobility and sensory function was observed in patients with mandible and tongue and/or floor-of-mouth tumors. Better tongue force and sensory function (thermal and tactile) positively influenced masticatory performance, and this effect was stronger where fewer occlusal units were present. The effect of both the tongue force and maximum bite force was weaker in dentate patients in comparison with patients with full dentures. A web-based application was developed to enable readers to explore our results and provide insight into the coherence between the found factors in the mixed model.Conclusions: Tongue function deteriorates after oral oncological treatment, without statistically significant recovery. Adequate bite and tongue forces are especially important for patients with a poor prosthetic state. Patients with sensory tongue function deficits especially benefit from the presence of more occluding pairs.